2020
DOI: 10.1002/cne.25012
|View full text |Cite
|
Sign up to set email alerts
|

Neural anatomy of echinoid early juveniles and comparison of nervous system organization in echinoderms

Abstract: The echinoderms are a phylum of marine deuterostomes characterized by the pentaradial (five fold) symmetry of their adult bodies. Due to this unusual body plan, adult echinoderms have long been excluded from comparative analyses aimed at understanding the origin and evolution of deuterostome nervous systems. Here, we investigated the neural anatomy of early juveniles of representatives of three of the five echinoderm classes: the echinoid Paracentrotus lividus, the asteroid Patiria miniata, and the holothuroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 121 publications
8
26
0
Order By: Relevance
“…Sea urchin has been used for over a hundred years as a model organism in developmental biology research (Wilson, 1895). Knowledge of sea urchins in the field of biology has expanded to include (1) the effects of toxic substances on their immune system, reproduction, and development (Nobre et al, 2015;Brown et al, 2020;Pikula et al, 2020;Rendell-Bhatti et al, 2021), (2) the gene expression involved in sea urchin fertilization and development stages (Li et al, 2020;Wessel et al, 2021;Cui et al, 2022), (3) the nervous system (Wood et al, 2018;Martín-Durán and Hejnol, 2021;Formery et al, 2021), and (4) sea urchin genomes (Sodergren et al, 2006;Kudtarkar and Cameron, 2017;Kinjo et al, 2018;Warner et al, 2021). Sea urchins have also been studied in various aspects related to the impact of current changing environments, such as ocean acidification and global warming to their development and growth (Dworjanyn and Byrne, 2018;García et al, 2018;Zhao et al, 2018;Houlihan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sea urchin has been used for over a hundred years as a model organism in developmental biology research (Wilson, 1895). Knowledge of sea urchins in the field of biology has expanded to include (1) the effects of toxic substances on their immune system, reproduction, and development (Nobre et al, 2015;Brown et al, 2020;Pikula et al, 2020;Rendell-Bhatti et al, 2021), (2) the gene expression involved in sea urchin fertilization and development stages (Li et al, 2020;Wessel et al, 2021;Cui et al, 2022), (3) the nervous system (Wood et al, 2018;Martín-Durán and Hejnol, 2021;Formery et al, 2021), and (4) sea urchin genomes (Sodergren et al, 2006;Kudtarkar and Cameron, 2017;Kinjo et al, 2018;Warner et al, 2021). Sea urchins have also been studied in various aspects related to the impact of current changing environments, such as ocean acidification and global warming to their development and growth (Dworjanyn and Byrne, 2018;García et al, 2018;Zhao et al, 2018;Houlihan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2007) and Formery et al. (2020) for the decalcification procedure. Note: This dehydration step may act as “post‐fixation”. In the original protocol (Amemiya et al., 2019), this step was designed for long‐term sample storage.…”
Section: Tipsmentioning
confidence: 99%
“…Nerve structures, such as neurons located in the apical organ and tracts of axons associated with the ciliary bands were identified during the larval development stage in echinoderms, which matches reports for hemichordate larvae [ 12 , 15 , 16 ]. In recent years, the development of genomic resources and molecular methods have allowed great progress for understanding the mechanisms of neurogenesis in the larvae of many echinoderm species, including the echinoids Strongylocentrotus purpuratus , Paracentrotus lividus , the asteroids Patiria miniata , Asterias rubens , the ophiuroids Amphipholis kochii , the crinoids Antedon mediterranea , Metacrinus rotundus , Anneissia japonica , and also the holothuroids Apostichopus californicus , Apostichopus parvimensis and Apostichopus japonicus [ 2 , 13 , 17 , 18 , 19 , 20 , 21 , 22 ]. These studies all indicated that the larval nervous system shows unexpected diversity in cell and fiber types and their distribution in both central and peripheral nervous components [ 2 , 13 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of genomic resources and molecular methods have allowed great progress for understanding the mechanisms of neurogenesis in the larvae of many echinoderm species, including the echinoids Strongylocentrotus purpuratus , Paracentrotus lividus , the asteroids Patiria miniata , Asterias rubens , the ophiuroids Amphipholis kochii , the crinoids Antedon mediterranea , Metacrinus rotundus , Anneissia japonica , and also the holothuroids Apostichopus californicus , Apostichopus parvimensis and Apostichopus japonicus [ 2 , 13 , 17 , 18 , 19 , 20 , 21 , 22 ]. These studies all indicated that the larval nervous system shows unexpected diversity in cell and fiber types and their distribution in both central and peripheral nervous components [ 2 , 13 , 17 , 18 , 19 , 20 , 21 , 22 ]. Among echinoderms, the planktotrophic holothuroid sea cucumbers retain both the ancestral body plan and the ancestral nervous system developmental pattern of echinoderms: a lack of neural precursor migration in the embryo and a feeding initiation stage-auricularia followed by a doliolaria stage [ 11 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation